RELIGIOSITY TOWARDS GUILTY FEELINGS MODERATED BY SELF-CONCEPT - Rostati; Siti Aisyah; Patisina (RADJA PUBLIKA, 2024)
The aim of this research is to determine the influence of religiosity on guilty feelings which is moderated by self-concept in detainees at the Belawan Police detention center. A total of 200 samples of prisoners were in the Belawan Police detention center. The sample was selected proportionally by random sampling. Data was obtained through a questionnaire. The data analysis technique uses structural equation modeling (SEM) with Smart-PLS version 3.0. The research results show that religiosity has a significant positive effect on guilty feelings, with an effect of 0.615 (61.5%). Religiosity also has a significant positive effect on self-concept with an influence size of 0.997 (99.7%). Meanwhile, self-concept has a significant negative effect on guilty feelings of -0.623 (-62.3). In the mediating role, it was found that self-concept was unable to moderate the influence of religiosity on guilty feelings, because the influence was only 0.003. The biggest influence that can influence the Guilty Feeling variable in police detention in Belawan is the Religiosity variable. Meanwhile, the negative influence of self-concept on guilty feelings means that prisoners' awareness needs to be increased, so that the more they are aware of their self-concept, the prisoners will be able to accept the situation, that they will regret and also change, so that they will not make the same mistakes they have made. . The suggestions given are to work together to build and increase the level of religiosity or religious values ​​and provide input related to a positive self-concept to the prisoners. Incorporating religious values ​​including; ideological dimension, ritual dimension, intellectual involvement, experienced dimension and consequential dimension. By increasing the religious values ​​of prisoners, the hope is to increase the level of self-awareness of prisoners, especially at the Belawan Police Detention Center.